Antagonism between representationism and abstractionism in antioqueño art - Arango Restrepo, Sofia Stella (Estudios de Filosofía, 2000)
Between 1945 and 1965, Medellin witnessed the struggle of opposed attitudes about the problems of Modern Art. Abstract art was rejected in the artistic environment, it was not considered as an acceptable means of self expression. This retarding view point let the Antioqueño art almost completely outside the renovation undergone by the art elsewhere in the nation. Exceptions to this during that period are the works of Fernando Bolero and Aníbal Gil.